Modern approaches to the organization children's and youth basketball: abroad experience - Oksana Komotska; Ruslana Sushko (Kharkiv State Academy of Physical Culture, 2022)
Purpose: the high level of basketball players' individual skill at the international arena requires radical changes in the approaches to the preparation of a high-quality reserve and the enlargement of the Ukrainian children's and youth basketball system, taking into account modern world trends in the evolution of the game. The study of practical experience and the generalization of the foreign specialists' opinions will contribute to the buildout of a high-quality training process of young basketball players. The aim of the study is to summarize the modern features of the organization of children's and youth basketball based on the study of the professional opinions of foreign coaches. Material and methods: 10 foreign basketball coaches who have been engaged in the international youth competitions, who got high results in the championships of their own countries and trained young players in youth national teams, were chosen as qualified experts. They were proposed to answer 10 questions in special questionnaire regarding the modern trends in the youth basketball. Theoretical analysis and generalization of data from scientific and methodological literature, and Internet resources, questionnaires in Google form using the ranking method, and the method of expert evaluations were applied in the research. Results: the opinions of foreign coaches who successfully work with young basketball players were studied and summarized. That made it possible to determine the current trends in the development of children's and youth basketball. Consistency of experts' opinions was confirmed using Kendall's concordance coefficient, all examinations were confirmed, experts' opinions were agreed. Conclusions: the priority objects of the examination were formed according to the distribution of experts' evaluations, namely: preference was given to the experience of the USA as a reference point for the evolution of basketball; the young basketball players' training system as a combination of education and training with multi-level selection on the basis of a basketball school (academy) is idealized; the overwhelming majority chose the focus on planning the educational and training process taking into account modern approaches to the psychological characteristics of young basketball players as a priority component; a common vision was expressed regarding the selection of players for the teams entered in the national championships, which should take place taking into account the combination of current skill and prospects for realizing individual potential; the existing need for scientific substantiation of a new style of management, taking into account the peculiarities, needs, motives and interests of the individual, is indicated.